Pengaruh Struktur Modal, Ukuran Perusahaan, Profitabilitas, Likuiditas, terhadap Nilai Perusahaan (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2017) - Nur Rohmah Nasrun; S Suyatmin (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2020)
The study purposes to determine the effect of capital structure, company size, profitability, and liquidity to the value of the company. This study obtained data directly by using secondary data from annual report of companies on website www.idx.co.id. Population in this study were all manufacturing companies listed on IDX between 2014-2017. This study obtained 332 manufacturing companies as sample by using purposive sampling method. This study using multiple linier regression as a data analysis method. The result shows that liquidity has significant to the value of the company. Capital structure, company size, and profitability have no significant to the value of the company.